Barriers and facilitators to treating insomnia in children with autism spectrum disorder and other neurodevelopmental disorders: Parent and health care professional perspectives. (December 2020) - Tan-MacNeill, Kim M.; Smith, Isabel M.; Jemcov, Anastasija; Keeler, Laura; Chorney, Jill; Johnson, Shannon; Weiss, Shelly K.; Begum, Esmot Ara; Brown, Cary A.; Constantin, Evelyn; Godbout, Roger; Hanlon-Dearman, Ana; et al.
Highlights: Sleep problems negatively affect children with neurodevelopmental disorders. Treatment is needed but parents experience barriers to access and implementation. Healthcare providers lack sufficient training and knowledge about sleep in NDDs. Increased awareness about sleep in NDDs and accessible interventions is needed. Transdiagnostic approach to sleep treatment holds potential for children with NDDs. Abstract: Background/aims: Insomnia is highly prevalent in children with neurodevelopmental disorders (NDDs), yet little research exists on sleep treatment access, utilization, and provision in this population. This study explores barriers and facilitators to access, use, and provision of treatment for sleep problems as experienced by parents of children with NDDs, including Autism Spectrum Disorder (ASD), Attention-Deficit/Hyperactivity Disorder (ADHD), Cerebral Palsy (CP) and Fetal Alcohol Spectrum Disorder (FASD), and health care professionals who work with children with these conditions. Method: Transcripts from online focus groups and interviews, conducted separately with parents of children with NDDs ( n = 43) and health care professionals ( n = 44), were qualitatively analyzed using content analysis for key themes. Results: Barriers included limited access to/availability of treatment, lack of knowledge/training, NDD-specific factors (e.g., symptoms, medications, and comorbidities), parent factors (e.g., capacity to implement treatment, exhaustion), and the challenging, intensive nature of sleep treatment. Facilitators included positive beliefs and attitudes, education, support, and ability to modify treatments for NDD symptoms. Barriers and facilitators were similar across all four NDDs. Conclusions: Results highlight a need for more education about sleep in NDDs and to develop accessible interventions, as well as the potential of a transdiagnostic approach to sleep treatment in this population.